Transcriptional Activity of HTLV-I Tax Influences the Expression of Marker Genes Associated with Cellular Transformation - Lemoine, Francene J. (IOS Press, 2001)
Human T cell leukemia virus type I (HTLV-I) has been identified as the etiologic agent of adult T cell leukemia (ATL). HTLV-I encodes a transcriptional regulatory protein, Tax, which also functions as the viral transforming protein. Through interactions with a number of cellular transcription factors Tax can modulate cellular gene expression. Since the majority of Tax-responsive cellular genes are important regulators of cellular proliferation, the transactivating functions of Tax appear to be necessary for cellular transformation by HTLV-I. Gaining a complete understanding of the broad range of genes regulated by Tax, the temporal pattern of their expression, and their effects on cell function may identify early markers of disease progression mediated by this virus.